Impact of customer default on cash conversion cycle and net working capital in construction company - Maesaroh, Maya; Faturohman, Taufik (International Journal of Financial, Accounting, and Management, 2024)
Purpose: This study aimed to determine the effect of customer default on the Cash Conversion Cycle and Net Working Capital in construction companies. Method: This study uses secondary data from companies’ financial reports to calculate the Cash Conversion Cycle, Net Working Capital, and Spearman's rho Correlation Test to determine the relationship between the two variables. Results: The results show that SOE customer default affects the condition of the Cash Conversion Cycle, especially in 2023, where the Cash Conversion Cycle value in Q123 (85 days) and Q223 (64 days), but the worst Cash Conversion Cycle results during the observation period are in Q122 (134 days). In Net Working Capital, there are only three periods with negative results: Q219 (-3.1B), Q319 (-461M), and Q421 (-4B), but not in 2023, because in 2023, the result is positive (or liquid). Spearman's rho Correlation Test shows that the relationship between the two variables is negatively correlated by -0.319, and the significance is 0.184, or the two variables are not significant. Limitations: This study was limited to construction companies in Bandung. The data taken from 2019 to Q3-2023 only focus on the influence of SOE customer defaults on the company's Cash Conversion Cycle and Net Working Capital.   Contribution: This study provides the best solution to the problem of customer default in the Cash Conversion Cycle and Net Working Capital in a construction company. If the solution is applied to the company, an implementation plan is created to fix the problem.